2013
DOI: 10.1016/j.molimm.2013.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of plasma membrane integrity, complement response and formation of reactive oxygen species during early myocardial ischemia/reperfusion

Abstract: Loss of plasma membrane integrity (LPMI) is a hallmark of necrotic cell death. The involvement of complement and ROS in the development of LPMI during the early stages of murine myocardial ischemia-reperfusion injury was investigated. LPMI developed within 1 hour of reperfusion to a level that was sustained through 24 hours. C3 deposition became significant at 3 hours’ reperfusion and thus contributed little to LPMI prior to this time. SOD1 transgenic mice had significantly less LPMI compared with WT mice at 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 32 publications
2
19
0
1
Order By: Relevance
“…MDA and LDH, which are biological products of ROS and lipid peroxidation, indicate the degree of lipid peroxidation in the body and subsequently indirectly reflect the degree of myocardial injury (24). SOD and CAT are the main antioxidant enzymes responsible for the mobilization of free radicals (25). The present study revealed that IPA decreased LDH and MDA levels and increased SOD and CAT activities in myocardial tissues and serum samples, confirming the myocardial protection of IPA through the inhibition of lipid peroxidation and increased ROS removal.…”
Section: Discussionsupporting
confidence: 77%
“…MDA and LDH, which are biological products of ROS and lipid peroxidation, indicate the degree of lipid peroxidation in the body and subsequently indirectly reflect the degree of myocardial injury (24). SOD and CAT are the main antioxidant enzymes responsible for the mobilization of free radicals (25). The present study revealed that IPA decreased LDH and MDA levels and increased SOD and CAT activities in myocardial tissues and serum samples, confirming the myocardial protection of IPA through the inhibition of lipid peroxidation and increased ROS removal.…”
Section: Discussionsupporting
confidence: 77%
“…39 However, the significant downregulation of the humoral immune response concomitantly with both the alternative and classical complement pathway in our cohort would suggest that ischemia, in the absence of reperfusion, may not lead to an immediate increase in these pathways as previously described. This is supported by very low complement deposition ( C3d ) in brain-dead donor hearts that had ischemic injury without reperfusion, 40 by the lag in C3 deposition compared to the loss of plasma membrane integrity during early myocardial ischemia, 41 and by the initial decrease in serum C3 levels in pediatric cardiac surgical patients. 42 …”
Section: Discussionmentioning
confidence: 98%
“…Subsequent studies demonstrated increased expression for all of the classical complement cascade proteins in ischemic tissues (804, 876). Postischemic complement activation is triggered by release of subcellular membrane consistuents secondary to cell necrosis (127, 248, 461, 672). Complement depletion or treatment with function-blocking antibodies that target specific proteins in the cascade have proven to be very effective in limiting postischemic inflammation and tissue injury, and constitute some of the strongest evidence supporting a role for complement cascade in I/R (76, 167, 251, 522, 530, 739, 795, 838, 845, 904).…”
Section: Inflammation Plays a Prominent Role In The Reperfusion Compomentioning
confidence: 99%